2021
DOI: 10.1177/00220345211051599
|View full text |Cite
|
Sign up to set email alerts
|

The Type IX Secretion System and Its Role in Bacterial Function and Pathogenesis

Abstract: Porphyromonas, Tannerella, and Prevotella species found in severe periodontitis use the Type IX Secretion System (T9SS) to load their outer membrane surface with an array of virulence factors. These virulence factors are then released on outer membrane vesicles (OMVs), which penetrate the host to dysregulate the immune response to establish a positive feedback loop of chronic, inflammatory destruction of the tooth’s supporting tissues. In this review, we present the latest information on the molecular architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
(127 reference statements)
0
20
1
Order By: Relevance
“…Highly active genes within this transcriptome belong to T9SS mechanism and gliding motility ( Supplementary Table S4 ). Overall, 18 genes ( gldA , gldB , gldD , gldF , gldG , gldH , gldI , gldJ , gldK , gldL , gldM , gldN , sprA , sprE , sprF , sprT , porU and porV ), required for gliding motility and protein secretion, and/or involved in T9SS ( Hunnicutt and Mcbride, 2000 ; McBride and Braun, 2004 ; Braun et al, 2005 ; Lauber et al, 2018 ; McBride, 2019 ; Hennell James et al, 2021 ; Trivedi et al 2022 ; Veith et al, 2022 ), were identified among DEGs ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Highly active genes within this transcriptome belong to T9SS mechanism and gliding motility ( Supplementary Table S4 ). Overall, 18 genes ( gldA , gldB , gldD , gldF , gldG , gldH , gldI , gldJ , gldK , gldL , gldM , gldN , sprA , sprE , sprF , sprT , porU and porV ), required for gliding motility and protein secretion, and/or involved in T9SS ( Hunnicutt and Mcbride, 2000 ; McBride and Braun, 2004 ; Braun et al, 2005 ; Lauber et al, 2018 ; McBride, 2019 ; Hennell James et al, 2021 ; Trivedi et al 2022 ; Veith et al, 2022 ), were identified among DEGs ( Supplementary Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It appears to localise in a helical manner, and it was proposed to be associated with the track on which SprB is propelled [ 37 , 38 ]. SprF may link SprB, directly or indirectly, to this track, which we recently proposed to also include the GldK and GldN proteins [ 39 ] ( Figure 7 B) that were pulled down at a slightly higher abundance than GldJ ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…These finding have led to a model in which PMF-energy transduction regulates the activation states of the PorLM and GldLM translocation motors ( 14 , 25 ). Upon sensing of the PMF, PorLM and GldLM transduce PMF energy in the form of conformational changes in the periplasmic domains of PorM and GldM as a prerequisite for substrate secretion or gliding motility ( 25 , 26 ). In this context, we propose that the visualized conformational classes of the PorKMN complexes correspond to different activation states of the motors.…”
Section: Resultsmentioning
confidence: 99%